Find two numbers which differ by 4 and whose product is 45.
- print Print
- list Cite
Expert Answers
calendarEducator since 2011
write2 answers
starTop subject is Math
Let's call the first number N1 and the second number N2.
So, let's call N1 the smaller number and N1=x
Let's call N2 the larger number and N2=x+4.
X(X+4)=45
x^2+4x=45
x^2+4x-45=0
(x+9)(x-5)=0
X=-9, X=5
Related Questions
- Find two numbers whose sum is 26 and whose product is 165
- 1 Educator Answer
- Find two numbers whose difference is 5 and the product is the least possible.
- 1 Educator Answer
- Find two numbers whose sum is 16 and whose product is a maximum.
- 1 Educator Answer
- Find the minimum product of two numbers whose difference is nine.
- 2 Educator Answers
- Find two integers whose difference is 12 and whose product is a minimum.
- 1 Educator Answer
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
We will assume that the numbers are x and y.
Given that the difference between the numbers is 4.
==> x - y = 4 .............(1)
Also, given the product of the numbers is 45.
==> x*y = 45................(2)
Now we will use the substitution method to solve.
From (1), we know that x = y + 4.
==> x*y = 45
==> (y+4)*y = 45
==> y^2 + 4y = 45
==> y^2 + 4y - 45 = 0
Now we will solve the quadratic equation using factors.
==> (y+ 9)(y-5) = 0
==> y1= -9 ==> x1= -5
==> y2 = 5 ==> x2= 9
Then the numbers are 5 and 9 OR -5 and -9.
calendarEducator since 2010
write12,554 answers
starTop subjects are Math, Science, and Business
The two numbers to be determined have a difference of 4, so let them be A and A + 4.
Now we are given that their product is 45
=> A*( A + 4) = 45
=> A^2 + 4A = 45
=> A^2 + 4A - 45 = 0
=> A^2 + 9A - 5A - 45 = 0
=> A( A + 9) - 5(A + 9) = 0
=> (A - 5)(A +9) = 0
This gives A = 5 and A = -9
So the two numbers are 5 , 9 and -9, -5
The required numbers can be (5, 9) and (-9, -5)
Let x and x+ 4 be the two numbers which differ by 4. Their product is 45.
So x(x+4) = 45.
=> x^2+4x-45 = 0
(x-5)(x+9)) = 0.
So x - 5 = 0, or x+9 = 0.
So x -5 = 0 gives x = 5. So the other number is x+4 = 9.
So x+ 9 = 0 gives x = -9 and the other number is -9+4 = -5.
Therefore the solution is (5 and 9) or ( -9 and -5).
Student Answers